Journeying with Ken Plummer through radical constructionism, critical humanism and intimate counterpublics. (June 2023) - Klesse, Christian
Ken Plummer's life work has had a major impact on the development of the sociology of sexuality. While being firmly rooted in and committed to the traditions of pragmatism and symbolic interactionism – which chimes nicely with his philosophical stance of critical humanism – Ken Plummer openly engaged in a critical dialogue with many theoretical perspectives. This renders his work a rich resource for researchers working on sexualities from within different paradigms. This paper engages in a critical appraisal of some of Plummer's most significant concepts through autobiographical reflection on my personal experience of working with Ken Plummer as a PhD student, further tracing the influence his work has had on my own writing on consensual non-monogamies, LGBTQIA + activism and queer film festivals. Using autoethnography and memory work, the essay highlights the powerful potential residing in Plummer's path-breaking contributions to social constructionism (script theory and narrative power), methodology (personal documents), narrative sociology (sexual stories), critical humanism (dialogical ethics and cosmopolitan sexualities) and political sociology (intra-movement conflict, intimate citizenship, counterpublics and age standpoints). The essay argues that these ideas – and Plummer's overall legacy as a scholar and theorist – bear a strong significance for future research in sexuality studies.